NMR case studies data analysis of complicated molecules - Simpson, Jeffrey H. (Amsterdam, Netherlands Elsevier, 2017)
NMR Case Studies: Data Analysis of Complicated Molecules provides a detailed discussion of the full logical flow associated with assigning the NMR spectra of complex molecules, also helping readers further develop their NMR spectral assignment skills. The robust case studies present the logic of each assignment, from beginning to end, fully exploring the available range of potential solutions. Readers will gain a better appreciation of various approaches and develop an intuitive sense for when this particular concept should be implemented, thus enhancing their skillsets and providing a host of methodologies potentially amenable to yielding correct assignments. Authored by a scientist with more than 20 years of experience in research and instruction, this book is the ideal reference for anyone in search of application-based content. The book addresses complicated molecules, including corticosteroids, biomolecules, polypeptides, and secondary metabolites.--Provided by publisher.
Chapter 1 - Introduction to the Methods of Nuclear Magnetic Resonance -- Chapter 2 - Corticosteroids -- Chapter 3 - Alkaloids, Nonsteroidal Hormones, Drugs, and Glycosides -- Chapter 4 - Two Twenty-Carbon Natural Products, One With an Unknown Structure -- Chapter 5 - Bigger and More Complicated Molecules -- References -- Index.
Includes bibliographical references (page 223) and index.
Keywords: Nuclear magnetic resonance; Electronic books